2016
DOI: 10.15403/jgld.2014.1121.253.ibs
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Interventions for Irritable Bowel Syndrome

Abstract: Irritable bowel syndrome (IBS) patients often present psychoform symptoms or psychiatric disorders. Among the psychological factors studied in IBS patients, two seem to influence mostly its severity: catastrophizing and somatization. Somatization is an independent risk factor for IBS. In addition, somatization more than the severity of IBS influences the way the patients perceive their illness, the outcome and the efficacy of treatment. Irritable bowel syndrome patients demonstrate greater catastrophizing scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 61 publications
(92 reference statements)
0
17
0
8
Order By: Relevance
“…It can be also used to address a large number of clinical conditions at both acute and chronic stages of disease expression, ranging from treatment of phobias and affective disorders (e.g., depression or posttraumatic stress disorder) to neuropsychiatric disorders, such as dissociative identity disorder, psychosis, anorexia nervosa, and somatic symptom disorder (Lynn et al, 2010). As an alternative approach for multiple medical conditions, hypnosis has also a well-established evidence of treating and managing a spectrum of painful conditions (Vanhaudenhuyse et al, 2015(Vanhaudenhuyse et al, , 2018, such as dilation and curettage (Fathi et al, 2017), irritable bowel syndrome (Gonsalkorale et al, 2003;Surdea-Blaga et al, 2016), phantom limb (Oakley and Halligan, 2002), migraine (Flynn, 2018), cancer-related pain (Vickers and Cassileth, 2001;Carlson et al, 2018), and pain related to multiple sclerosis (Amatya et al, 2018). A common denominator for these interventions is the involvement of the cingulate cortex (Vogt and Brent, 2009).…”
Section: The Merits Of Hypnosis In Clinical Applicationsmentioning
confidence: 99%
“…It can be also used to address a large number of clinical conditions at both acute and chronic stages of disease expression, ranging from treatment of phobias and affective disorders (e.g., depression or posttraumatic stress disorder) to neuropsychiatric disorders, such as dissociative identity disorder, psychosis, anorexia nervosa, and somatic symptom disorder (Lynn et al, 2010). As an alternative approach for multiple medical conditions, hypnosis has also a well-established evidence of treating and managing a spectrum of painful conditions (Vanhaudenhuyse et al, 2015(Vanhaudenhuyse et al, , 2018, such as dilation and curettage (Fathi et al, 2017), irritable bowel syndrome (Gonsalkorale et al, 2003;Surdea-Blaga et al, 2016), phantom limb (Oakley and Halligan, 2002), migraine (Flynn, 2018), cancer-related pain (Vickers and Cassileth, 2001;Carlson et al, 2018), and pain related to multiple sclerosis (Amatya et al, 2018). A common denominator for these interventions is the involvement of the cingulate cortex (Vogt and Brent, 2009).…”
Section: The Merits Of Hypnosis In Clinical Applicationsmentioning
confidence: 99%
“…For the physical component of QoL, the finding on the involvement of negative mood in QoL impairment is in line with previous studies (Lee et al, 2008;Muscatello et al, 2014Muscatello et al, , 2016Pellissier et al, 2010;Rey, Garcia-Alonso, Moreno-Ortega, Alvarez-Sanchez, & Diaz-Rubio, 2008;Spiegel et al, 2004) which reported a significant impact of psychological distress (anxiety, depression, negative mood, somatization, stress) on QoL, as well as on symptom severity. The resulting consensus on the importance of psychological distress has shaped the vast majority of psychological interventions, most of which predominantly focus on QoL improvement and symptom alleviation through the reduction of psychological distress (Surdea-Blaga et al, 2016). Because of this, the most interesting finding of this study is the significance of positive mood for predicting mental QoL.…”
Section: Discussionmentioning
confidence: 92%
“…When Engel (Engel, 1977) proposed the biopsychosocial (BPS) model of health and disease, the door for understanding functional disorders opened. Accordingly, this model provides the conceptual basis for defining, understanding, and treating functional gastrointestinal (GI) disorders (Drossman, 1998;Drossman, Camilleri, Mayer, & Whitehead, 2002;Drossman & Hasler, 2016;Surdea-Blaga, Baban, Nedelcu, & Dumitrascu, 2016). It is now clear that irritable bowel syndrome (IBS), one of the most common functional GI disorders, results from complex bi-directional interactions of biological, psychological, and social factors (Muscatello, Bruno, Scimeca, Pandolfo, & Zoccali, 2014;van der Veek, Dusseldorp, van Rood, & Masclee, 2010;van Tilburg, Palsson, & Whitehead, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…If symptoms persist, subsequent medication trials could include alosetron, eluxadoline or a bile acid sequestrant [ 8 , 9 ]. Interventions such as gut directed hypnotherapy and cognitive behavioral therapy can also be considered in select patients [ 20 ]. The patient should be asked to call the office for a quick follow-up approximately 4 weeks after initiating therapy.…”
Section: Case Study: Managementmentioning
confidence: 99%